Next Generation Aqueous Two‐Phase System for Gentle, Effective, and Timely Extracellular Vesicle Isolation and Transcriptomic Analysis - Boyang Su; Morteza Jeyhani; Gobi Thillainadesan; Minzhi Sheng; Reese Wunsche; Thamara Dayarathna; Kristin Cimolai; Hanyi Weng; Katarzyna J. Jerzak; Stanley K. Liu; Scott S. H. Tsai; Hon S. Leong (Journal of Extracellular Vesicles)
ABSTRACT The isolation of extracellular vesicles (EVs) using currently available methods frequently compromises purity and yield to prioritize speed. Here, we present a next‐generation aqueous two‐phase system (next‐gen ATPS) for the isolation of EVs regardless of scale and volume that is superior to conventional methods such as ultracentrifugation (UC) and commercial kits. This is made possible by the two aqueous phases, one rich in polyethylene glycol (PEG) and the other rich in dextran (DEX), whereby fully encapsulated lipid vesicles preferentially migrate to the DEX‐rich phase to achieve a local energy minimum for the EVs. Isolated EVs as found in the DEX‐rich phase are more amenable to biomarker analysis such as nanoscale flow cytometry (nFC) when using various pre‐conjugated antibodies specific for CD9, CD63 and CD81. TRIzol RNA isolation is further enabled by the addition of dextranase, a critical component of this next‐gen ATPS method. RNA yield of next‐gen ATPS‐isolated EVs is superior to UC and other commercial kits. This negates the use of specialized EV RNA extraction kits. The use of dextranase also enables more accurate immunoreactivity of pre‐conjugated antibodies for the detection of EVs by nFC. Transcriptomic analysis of EVs isolated using the next‐gen ATPS revealed a strong overlap in microRNA (miRNA), circular RNA (circRNA) and small nucleolar RNA (snoRNA) profiles with EV donor cells, as well as EVs isolated by UC and the exoRNeasy kit, while detecting a superior number of circRNAs compared to the kit in human samples. Overall, this next‐gen ATPS method stands out as a rapid and highly effective approach to isolate high‐quality EVs in high yield, ensuring optimal extraction and analysis of EV‐encapsulated nucleic acids.